Evaluation of cumulative radiation dose in neonates in neonatal surgery ward of Alzahra Hospital of Isfahan - Masood Nazem Masood Nazem; Daryoush Shahbazi-Gahrouei; Mohamad reza Sharbafchi; Mohamad Saleh Jafarpishe; Mehrdad Hosseinpour (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2018)
Introduction: The purpose of this study, is evaluation of the average of cumulative radiation exposure in admitted neonates in neonatal surgery ward. Materials and methods: Participants were all neonates consecutively admitted to the neonatal surgery unit of the study hospital for surgery and need one type of radiological study during hospitalization. Thermo luminescent dosimeters (TLD GR200) were used for evaluating absorbed dose of radiation on the body. For controlling of confounding variables, 130 admitted neonates who need no radiation were selected as control group. Results: In this study, we evaluated 169 neonates.The most x -ray examination was on ribcage (338 cases). Total amount of bowel and backbone x-ray examinations were 117 and 11 respectively. Total amount of contrast enema, meal and swallow was 8, 9 and 5 respectively. The cumulative absorbed dose in 19 patients was more than 10 mSv. There was a significant differences between control group with other x ray examination groups (p=0.001). The mean of accumulated received dose for patients during admission period was 3.13±5.12 mSv. Conclusion: The average of accumulated received dose for neonates was about 3.13 mSv. Although this dose is less than annual limit dose, but it is inacceptable in comparison with other medical centers.